Development of a Project-Based Learning (PjBL) Student Worksheet with a Scientific Daily Life Context on the Topic of Acid, Base, and Salt Solutions - Miterianifa; Adibah, Bunga; Syarif, Muhammad Ilham; Trisnayanti, Yetty (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This research was motivated by the limited availability of teaching materials in the form of project-based learning (PjBL) student worksheets that integrate scientific concepts with daily life contexts. The purpose of this study was to develop PjBL-based student worksheets contextualized to everyday scientific phenomena for the topic of acid, base, and salt solutions at the junior high school/Islamic junior high school level. The study employed a research and development (R&D) design using the Plomp model. Both qualitative and quantitative data were collected through questionnaires, interviews, and documentation. The validation results indicated that the developed product was highly valid, with scores of 100% from language experts, 92% from subject matter experts, and 72% from teaching material experts, yielding an overall mean validity score of 88%. In terms of practicality, teachers rated the product as very practical with a score of 91%, while students evaluated it as very good with a score of 93%. Based on these findings, it can be concluded that the PjBL-based student worksheets with a scientific daily life context for the acid, base, and salt solutions lesson are valid, practical, and suitable for use in science learning at the junior high school/Islamic junior high school level.